KONSEP DASAR KEPEMIMPINAN DALAM ORGANISASI SECARA UMUM DAN ORGANISASI PENDIDIKAN - Hidayani , Putri; Indriani, Indriani (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2024)
This journal discusses the fundamental concept of leadership in organizations in general and examines its application in the context of educational organizations. The research method used in this study is a literature review, involving data and information retrieval from various sources in the literature as research data sources. This research explores the role of leaders in achieving organizational goals, compares various leadership theories, and analyzes the impact of leadership on organizational performance and student learning outcomes. The research findings identify key factors that support effective leadership in an educational environment. This study provides valuable insights for educational practitioners and organizational leaders in understanding the vital role of leadership in achieving organizational success